The key 1000 life-changing days - Flavia Indrio; Angelo Pietrobelli; Vanessa Nadia Dargenio; Flavia Marchese; Assunta Grillo; Mehmet Vural; Ida Giardino; Massimo Pettoello-Mantovani (Elsevier, 2023)
The first 1,000 days of life represent the period between conception and the age of two years. It is possible to identify, within the first 1,000 days, some basic periods of development: pre-conception and conceptional, first trimester of pregnancy, second and third trimesters of pregnancy, labor-birth, first month of life, first year of life, and second year of life. During this period, the foundations are laid for proper physical and psychological development of the child; therefore, putting in place appropriate preventive measures specific to each stage allows the child's future to be built, influencing its entire future existence. The purpose of this brief overview is to emphasize some important aspects of this period that is fundamental to the child's future life.